An ultra high performance multi-element doped mesoporous carbon catalyst derived from poly(4-vinylpyridine). Issue 46 (28th October 2015) - You, Chenghang; Dang, Dai; Qiao, Xiaochang; Wang, Guanghua; Fan, Wenjun; Chen, Rong; Li, Yingwei; Li, Xiuhua; Liao, Shijun
Abstract : An ordered mesoporous carbon catalyst derived from iron-complexed poly(4-vinylpyridine), with a much higher ORR performance than a commercial Pt/C catalyst. Abstract : A high performance doped carbon catalyst with ordered mesoporous structures and a high surface area (1217 m 2 g −1 ) was prepared through a nanocasting-pyrolysis procedure by using poly(4-vinylpyridine) and iron chloride as the precursors and SBA-15 as the template. The catalyst exhibited excellent oxygen reduction reaction (ORR) performance, and was far more active than a commercial Pt/C catalyst in alkaline media, with its half-wave potential (−0.083 V, vs. Ag/AgCl) 64 mV more positive and current density at −0.1 V ( vs. Ag/AgCl, −3.651 mA cm −2 ) almost three times higher than those of a commercial Pt/C catalyst (−0.147 V, vs. Ag/AgCl, and −0.967 mA cm −2 ), respectively. To our knowledge, it is one of the best carbon-based ORR catalysts to date in an alkaline medium. In addition to the outstanding ORR performance, our catalyst also illustrated excellent stability, methanol tolerance, and high catalytic efficiency. It is found that the total N contents and the compositions of each N species in the catalysts strongly depend on the pyrolysis temperatures. Furthermore, we found that the SBA-15 templates not only give catalysts well-defined mesoporous structures, but also seem to help increase the total N content whilst the proportion of each N species in the catalysts is not changed obviously.